Islam, Education, and Secularism: A Literature Review - Nuraeni, Heni Ani; Hirmah, Ni'ami Kamila; Jannah, Fiqra Sabil (Bestari, 2023)
Secularism is nothing more than an ethical system that teaches about the principles of life about what, how, and where humans live or how humans should behave in everyday life. Secularism teaches man to raise the standard of life that is beneficial by seeking good in the world through human abilities without reference to religion or doctrine. The primary purpose of this understanding of secularism is to separate worldly affairs from God's in all aspects of life, especially in the context of Education. This secularism has been widespread in Indonesia for a long time, since the arrival of the Dutch in a variety of missions, one of which is the issue of education. In the world, Dutch education implants a system of secularism, by separating religious life from worldly life, and religious education with general education, which then gives birth to a new education system in Indonesia. But in this journal the author's team focuses only on his research around the origins of secularism, the history of the births of the secularist, the influence of laicism in the world of education, the idea of seculation in the modern world, the Islamic state that has undergone a change in education, and laicity as the challenge of contemporary Islamic education, this secularity has entered and affected all aspects of life, especially in the aspect of education.